2017
DOI: 10.1002/uog.17337
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and histological measurements of dividing membrane thickness in twin gestations

Abstract: Prenatal ultrasound measurement of twin dividing membrane thickness is positively correlated with postnatal histological measurement. Dichorionicity can be determined by a magnified dividing membrane thickness ≥ 1.9 mm. Measurements with the ultrasound beam parallel to the dividing membrane may be more accurate than perpendicular measurements. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…is irregularly thickened 15.0 mm dividing membrane was not a normal variant, as the vast majority of dichorionic twins show thickness between 1.9 and 3.6 mm [2,3]. Di erential diagnosis could include a circumvallate placenta, an amniotic band, uterine synechiae, uterine congenital abnormalities, or membranes from a vanishing twin.…”
Section: Discussionmentioning
confidence: 99%
“…is irregularly thickened 15.0 mm dividing membrane was not a normal variant, as the vast majority of dichorionic twins show thickness between 1.9 and 3.6 mm [2,3]. Di erential diagnosis could include a circumvallate placenta, an amniotic band, uterine synechiae, uterine congenital abnormalities, or membranes from a vanishing twin.…”
Section: Discussionmentioning
confidence: 99%
“…When using 2-dimensional ultrasound, an intertwin membrane thickness of 1.5 to 2.0 mm may be inconclusive for MC twins. Bracero et al 9 reported that a cutoff value of 1.9 mm of the dividing membrane thickness is found to be the best predictor of chorionicity with the ultrasound beam parallel. However, there is still no consensus about the optimal cutoff value.…”
Section: Determination Of Chorionicity Of Twin Pregnancymentioning
confidence: 99%
“…Also, the impression of a false-positive lambda sign can be created when an umbilical cord insertion opens directly into the membrane between the fetuses [8]. Other described clues to determine chorionicity include membrane thickness measurement (≥ 1.9 mm dichorionic) [9], the number of membrane layers (2 thin amniotic membranes in monochorionic or 3 layers in dichorionic twins with 2 amniotic membranes and a chorionic layer in between) or determination of the fetal sexes [7].…”
Section: Datierung Der Zwillingsschwangerschaftmentioning
confidence: 99%
“…Auch kann der Eindruck eines falsch positiven Lambda-Zeichen entstehen, wenn ein Nabelschnuransatz direkt in die Membran zwischen den Föten mündet [8]. Weitere beschriebene Hinweiszeichen zur Festlegung der Chorionizität sind die Membrandickenmessung (≥ 1,9 mm dichorial) [9], das Zählen der Membranschichten (2 dünne Amnionmembranen bei monochorialen oder 3 Schichten bei dichorialen Zwillingen mit 2 Amnionmembranen und einer Chorionschicht dazwischen) oder die Bestimmung der fetalen Geschlechter [7].…”
Section: Noteunclassified